Pengaruh Self Efficacy, Adversity Quotient Dan Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Awalia, Riski; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the effect of self-efficacy, Adversity Quotient, and entrepreneurship education on increasing entrepreneurial intention. The object of this research is students of the Faculty of Economics and Business, Islamic University of Malang with a sample size of 82 students with a record of having taken entrepreneurship courses and not having a business. The sampling technique used was purposive sampling. Data collection techniques using questionnaires and data analysis tools This study uses a quantitative approach because the data is obtained in the form of numbers. Based on the results of research analysis simultaneously self efficacy positive and significant effect on entrepreneurial intentions. And adversity quotient simultaneously positive and significant effect on entrepreneurial intentions. Same with self efficacy, Adversity Quotient, entrepreneurship education simultaneously positive and significant effect on entrepreneurial intention. Keywords: Self Efficacy, Adversity Quotient, Entrepreneurship Education and Entrepreneurial Intention.